Effects of variable O2 concentrations and injection pressures on the combustion and emissions characteristics of the petro-diesel and hydrotreated vegetable oil-based fuels under the simulated diesel engine condition. Issue 6 (December 2018) - Vo, C.; Charoenphonphanich, C.; Karin, P.; Susumu, S.; Hidenori, K.
Abstract: This experimental research investigates the effects of variable O2 concentrations and injection pressures on the combustion and emissions characteristics of the diesel (B7) and the hydrotreated vegetable oil (HVO)-based fuels. The O2 concentrations included 21%, 15% and 10% O2, while the injection pressures were 80 and 120 MPa. The experimental fuels were the diesel fuel (B7), the neat HVO, the 20%, 50% and 80% HVO (by mass fraction) blended with the diesel. The experiments were carried out in a rapid compression-expansion machine (RCEM) under the direct injection (DI) diesel combustion condition. The analysis was undertaken using the two-color method. The experimental results indicated that the ignition delay, the heat release rate, the flame temperature, the soot density-KL factor, the NOx and soot-out emissions were inversely correlated to the HVO fraction in the blend. In addition, the findings revealed the similar flame profiles in which the higher flame temperature region and the darker KL density were concentrated around the spray flame upstream, regardless of the HVO mixing ratio. Besides, the decrease in the O2 concentration resulted in the lower heat release rate, integral heat release, flame temperature, KL factor and NOx emissions but the longer ignition delay and higher soot concentration, with the highest soot concentration observed under the 15% O2 environment. Nevertheless, the higher pressure differential (i.e. between the injection pressure and the ambient pressure) contributed to the shorter ignition delay, higher heat release rate, early peak of the flame temperature, wider combustion area, faster soot oxidation rate and higher NOx production. Highlights: Effects of O2 concentrations and injection pressures on combustion and emissions characteristics. Flame temperature and KL factor measured using two color method. Higher flame temperature and soot density were concentrated around the flame upstream. HVO produced lower flame temperature and KL factor than the others fuel. NOx and soot-out were inversely each other when adjusting O2 concentration and injection pressure.